Enhancing Middle School Teachers' Understanding of Locally Context-Based STEM Learning - Jamaludin Jamaludin; Marleny Leasa; Gazali Rachman; Efilina Kissiya Kissiya; Herman Semuel Wattimena; John Rafafy Batlolona (Pascasarjana Universitas Mataram, 2026)
This community service activity aims to improve junior high school teachers' understanding of implementing local context-based STEM learning in Makariki District, Central Maluku Regency. The activity was carried out using a participatory approach through the stages of needs analysis, training, implementation assistance, and evaluation. The training materials included STEM concepts, STEM integration, local context, and implementation, as well as the application of Project Based Learning (PjBL) and Engineering Design Process (EDP) in project-based learning. The results of the activity showed an increase in teachers' understanding of the STEM aspects provided. Teachers also demonstrated increased ability in designing project-based learning tools and utilizing local culture and environment as contextual and meaningful learning resources for students. In addition, interview results showed a change in teachers' mindsets towards more active, creative, collaborative learning, and relevant to students' daily lives. Thus, local context-based STEM training has proven effective in improving teachers' professional competence and supporting the development of innovative, contextual, and problem-solving-oriented 21st-century learning